Association between serum albumin and cognitive dysfunction in hepatic encephalopathy: An exploratory data analysis - Kosuke Kaji; Kiwamu Okita; Kazuyuki Suzuki; Ikuya Sato; Masaki Fujisawa; Hitoshi Yoshiji (JGH Open, 2021)
Abstract Background and Aim Because covert hepatic encephalopathy (CHE) has been shown to affect the prognosis of cirrhotic patients, early diagnosis of hepatic encephalopathy (HE) is a prerequisite for the preservation of patients' quality of life and for prophylaxis of overt HE. The aim of this study was to identify a clinical parameter to predict impairment of cognitive function in cirrhotic patients with early‐stage HE. Methods We investigated the data from 172 patients with cirrhotic or idiopathic portosystemic shunt (PSS) in phase II/III trials of rifaximin in Japan. Classification and regression trees (CARTs) were constructed to identify clinical profiles related to cognitive dysfunction as indicated by the prolongation of time required for the Number Connection Test (NCT‐B). Results CART analysis detected age 65 years as the variable for the initial split, and serum albumin level was selected as the variable for the second split among patients aged ≤65 years. In 27 cirrhotic patients aged ≤65 years without PSS, receiver operating characteristic curve analysis revealed that the optimal albumin level cutoff point was 3.05 g/dL, and the area under the curve was 0.80 for the prolongation of NCT‐B time, which was higher than that of the branched‐chain amino acids‐to‐tyrosine ratio (0.46), the prothrombin time–international normalized ratio (PT‐INR) (0.68), serum ammonia (0.61), and total bilirubin (0.69). Conclusions Lower serum albumin level as a clinical biomarker associated with impaired cognitive function may be available as a screening examination for early‐stage HE in cirrhotic patients aged ≤65 years without PSS before undergoing neuropsychological tests.